Investigate the Structural and Optical Properties of RF-Sputtered V2O5 thin films deposited at different Power - Noor Lafta. Hamdan; Faris S. Atallah; Mohammed K. Khalaf; Ibrahim K. Salman (Tikrit Journal of Pure Science, 2020)
In this work, the structural and optical properties of V2O5 have been presented. Thin films were manufactured by the RF magnetron sputtering process. The nanostructures and some optical properties  of deposit thin films at different sputtering RF power in a plasma chamber were investigated. The structural investigation was performed with  X-Ray Diffraction (XRD) measurements and Atomic Force Microscopy (AFM). The results obtained from both methods have revealed that as-deposited films were polycrystalline in nature. The texture of the films was observed  that , the crystallite and  grain size were increased with increasing the sputtering power. Optical properties were determined by transmission measurements in the spectral range from (250 to 1100 nm) . An Optical energy gap of sputtered films and its dependency to sputtering power of plasma have been measured. It was found that the energy gap decreased with increasing the  used power. The energy band gap was found to be in the ranged of (3.02 eV to 2.90 eV) when the sputtering power varying from (75 nm to 150 Watt).